The petroglyphs of El Chiral, Polobaya rock center - Tacca Quispe, Lorenzo W. (2011)
Interest in ancient cave paintings has grown tremendously in the last few years as a result of several recent discoveries. The petroglyph site, called El Chiral, stands out for the number and quality of drawings. The following article provides background on the pre-Columbian period in which these images were painted; analyzes the materials, techniques, and styles of design; reviews the different types of cave art found within the site, including their origins and functions; and finally, reproduces several images of the drawings and photographs of the petroglyphs.